2020
DOI: 10.1002/smll.202000301
|View full text |Cite
|
Sign up to set email alerts
|

Multigenerational Exposures of Daphnia Magna to Pristine and Aged Silver Nanoparticles: Epigenetic Changes and Phenotypical Ageing Related Effects

Abstract: Engineered nanoparticles (NPs) undergo physical, chemical, and biological transformation after environmental release, resulting in different properties of the "aged" versus "pristine" forms. While many studies have investigated the ecotoxicological effects of silver (Ag) NPs, the majority focus on "pristine" Ag NPs in simple exposure media, rather than investigating realistic environmental exposure scenarios with transformed NPs. Here, the effects of "pristine" and "aged" Ag NPs are systematically evaluated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 58 publications
5
16
0
Order By: Relevance
“…Increasing evidence suggests that the gradual increase in free radicals and oxidative stress with age is the Environmental Science: Nano Paper primary determinant of ageing. 64 The presence of ageing related proteins in the NMs coronas is consistent with the morphological evidence presented previously 34,65 that exposure to Ag NMs results in dramatic tail shortening and increased lipid droplets, two phenotypical traits of ageing, suggesting that the NMs induce accelerated ageing in the developing daphnids. Other proteins which have a high degree of species conservation that were linked to lipid transport, antioxidant processes and developmental processes are copper-zinc superoxide dismutase, vascular endothelial growth factor receptor, and S-adenosylmethionine synthase.…”
Section: Functions Of the Most Commonly Identified Proteins In The Nmsupporting
confidence: 88%
See 1 more Smart Citation
“…Increasing evidence suggests that the gradual increase in free radicals and oxidative stress with age is the Environmental Science: Nano Paper primary determinant of ageing. 64 The presence of ageing related proteins in the NMs coronas is consistent with the morphological evidence presented previously 34,65 that exposure to Ag NMs results in dramatic tail shortening and increased lipid droplets, two phenotypical traits of ageing, suggesting that the NMs induce accelerated ageing in the developing daphnids. Other proteins which have a high degree of species conservation that were linked to lipid transport, antioxidant processes and developmental processes are copper-zinc superoxide dismutase, vascular endothelial growth factor receptor, and S-adenosylmethionine synthase.…”
Section: Functions Of the Most Commonly Identified Proteins In The Nmsupporting
confidence: 88%
“…It was recently shown that the chronic (reproductive) ecotoxicity of Ag and TiO 2 NMs to Daphnia magna is dramatically reduced by environmental ageing of the NMs in media of different ionic strengths and natural organic matter contents. 33,34 Understanding the different proteins acquired by freshly dispersed (pristine engineered) and aged NMs in different environmentally relevant media, and their biological functions will provide important insights into their mechanisms of NM toxicity. Thus, as part of the overall assessment of the NMs chronic toxicity (Ellis et al, 2020 33 ), we characterised the secreted protein coronas that the NMs had acquired after 7 days in contact with Daphnia magna under each of the different medium conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[216] Furthermore, after aging for six months in environmentally realistic water containing NOM, there was a considerable reduction in the inhibitory effects on reproduction and antioxidant stressrelated genes on D. magna over four generations from pristine Ag NPs. [217] www.advancedsciencenews.com www.small-journal.com…”
Section: Genotoxicity and Reproductive Toxicitymentioning
confidence: 99%
“…Examples include the observation of the transfer of stress tolerance associated with gene expression changes linked with altered trimethylation of histone H3 lysine 9, identified as a mechanisms for transgenerational inheritance of the maintenance of stressor responses in C. elegans (Klosin et al, 2017) and heritable changes in a DNA methylation in Arabadopsis in response to nickel exposure (Li et al, 2015). A role of epigenetic mechanisms in heritable effects has also been identified in Daphnia magna in response to ionizing radiation (Jeremias et al, 2018;Trijau et al, 2018), silver nanoparticles (Ellis et al, 2020), uranium (Dias et al, 2008;Massarin et al, 2011;Dutilleul et al, 2014;Goussen et al, 2015) and a DNA methylation inhibitor (Lindeman et al, 2019). How these epigenetic mechanisms are linked to sensitivity is currently unknown.…”
Section: The Contribution Of Evolutionary Process To Species Sensitivitymentioning
confidence: 99%